Myths, Techno and Logos: aproaching the origin of Occidental science throughout Homer and Hesiod - Juana María Hernández Conesa; Paloma Moral de Calatrava; María Victoria Caballero Gómez (Universidad de Alicante, 2012)
Thought about the origins of Occidental Science take us back to Greece in VII and VI centuries b. C. Being the most splendor century the V century, well known as Pericles's century. It is there were first traces of occidental literature were found and protected. Those literary texts, root of measure and principles of reason and freedom are the basic foundation not only for artistic and literary creation purposes but capital works for meaning, reason for the origin of Occidental Science. Starting from a pre-scientific thought, means of influence in the origin of rational thought and thus scientific thought, are here analysed. The fundamental literary works were considerations here stated are based on are, on the one side: The Iliad and The Odyssey by Homer, and on the other side: Cosmogony and The works and the days by Hesiod. Differences and similarities of content in a socio-political context between those days and presently have been considered, as well as religious concepts - so much relevant and connected to Science in those historical dates - whose interest for our purposes forces our deepening in origins and postulates, which, to a certain extent, are still in force.